Variation in post‐adenotonsillectomy admission practices in 24 pediatric hospitals. (31st July 2013) - Goyal, Samita S.; Shah, Rahul; Roberson, David W.; Schwartz, Margot L.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis There is controversy about which children should be admitted after adenotonsillectomy (T&A) and limited clinical evidence to help with this decision. Current practice has evolved based on empirical or anecdotal evidence. We sought to identify practice variations in postoperative admission after T&A in tertiary care pediatric hospitals. Study Design Retrospective database study using administrative information stored in the Pediatric Health Information System (PHIS) database. Methods There were 29, 920 T&As performed in 24 pediatric hospitals included in the PHIS database between July 1, 2009 and June 30, 2010. Patients were identified as outpatient (discharged the same day) or inpatient (not discharged on the day of surgery). We examined admission rates across different hospitals stratified by age, obstructive sleep apnea (OSA), and other complex chronic conditions. Results Younger age, the existence of a complex chronic condition, and OSA were all associated with higher post‐T&A admission rates. Admission rates ranged from >94% for children under 2 years of age, with OSA and at least one medical comorbidity, to 14% for children older than 5 years, without OSA and without any medical comorbidities. Between‐hospital variability was extreme; for example, for 3 to 5 year olds, the admission rate varied from 5% to 90% between hospitals. Very significant variation remained even after controlling for age, comorbidities, and OSA. Conclusions Post T&A admission rates vary tremendously across comparable tertiary‐care pediatric hospitals. There is a crucial need for a better understanding of the risk of complications on the first postoperative night, and the appropriate indications for monitored admission on that night. Level of Evidence 4. Laryngoscope, 123:2561–2567, 2013